Fatty acid profile of Chlorella sorokiniana InaCC M38 grown in tofu wastewater for biofuel potential - DEVY SUSANTY; LUSI NURUL SAFITRI; RICSON PEMIMPIN HUTAGAOL; ADE AYU OKSARI; NURLELA NURLELA (Nusantara Bioscience, 2025)
Abstract. Susanty D, Safitri LN, Hutagaol RP, Oksari AA, Nurlela. 2025. Fatty acid profile of Chlorella sorokiniana InaCC M38 grown in tofu wastewater for biofuel potential. Nusantara Bioscience 17: 226-234. Chlorella sorokiniana Shihira & Krauss, 1965 is a microalgae that can grow in tofu liquid waste medium by utilizing the nutrients in the waste in the form of carbon (C), nitrogen (N), phosphorus (P), and potassium (K). This research aims to determine the lipid content and fatty acid compounds contained in C. sorokiniana cultured in 25, 30, and 35% Tofu Liquid Waste (TLW) medium using two extraction methods. In this study, the growth of C. sorokiniana on TLW medium was determined by calculating the cell density of C. sorokiniana using a hemocytometer, and the biomass was collected by centrifuging. Chlorella sorokiniana was cultivated for seven days. Lipid extraction was performed using maceration and a combined ultrasonic-assisted extraction (UAE)–maceration method. Biomass and lipid yields, as well as fatty acid methyl esters (FAME) profiles, were analyzed using GC–MS. Chlorella sorokiniana grows well on 30% TLW medium with a dry biomass weight of 0.45 g/L on day 7; extraction using the combined method extracted more fatty acid compounds than the maceration method. Lipid yield using the extraction by combined extraction method had more excellent results (4.61%) than the maceration method (3.82%). The fatty acid composition of C. sorokiniana extracted by combination extraction consists of 11 types of Saturated Fatty Acids (SFA), two types of Monounsaturated Fatty Acids (MUFA), and two types of Polyunsaturated Fatty Acids (PUFA). The Saturated fatty acid most commonly contained in C. sorokiniana was palmitic acid, which could be applied as biodiesel. Chlorella sorokiniana cultured in 30% TLW has a higher percentage of SFA (56.58%) with less PUFA, making it more potential for biodiesel.